Determine the Optimal Extent of Thyroidectomy and Lymphadenectomy for Patients With Papillary Thyroid Microcarcinoma - Feng, Jia-Wei; Pan, Hua; Wang, Lei; Ye, Jing; Jiang, Yong; Qu, Zhen (Frontiers in Endocrinology, 2019)
Background: The optimal extent of surgery, including lymph node dissection, remains controversial in papillary thyroid microcarcinoma (PTMC). Determining risk factors of central lymph node metastasis (CLNM) and recurrence-free survival (RFS) may help surgeons determine individualized surgery. Methods: A total of 353 patients with PTMC were retrospectively analyzed, including 263 with overt PTMC and 90 with incidental PTMC. The recurrence rate between different extent of thyroidectomy was compared. The relationship between CLNM and clinicopathologic factors was analyzed. Cox regression model was used to determine the risk factors for RFS. Results: Lobectomy/total thyroidectomy (TT) with central neck dissection (CND) was performed in 263 overt PTMC patients, and lobectomy/partial thyroidectomy was performed in 90 incidental PTMC patients. In 263 overt PTMC patients, 93 (26.3%) had CLNM only and 13 (3.7%) had both CLNM and lateral lymph node metastases (LLNM). Multifocal PTMC patients who underwent lobectomy had the higher rate of thyroid bed and lymph node recurrence than patients who underwent TT (P<0.05). Independent predictors for CLNM were age <45 years, tumor size >5 mm and presence of extrathyroidal extension (ETE). Tumor size >5 mm, multifocality, presence of ETE, presence of CLNM, and presence of LLNM were the significant factors related to the RFS. Conclusion: Fine-needle aspiration biopsy is advised to distinguish incidental PTMC from the benign nodules. For multifocal PTMC patients, TT should be performed to reduce the recurrence. Routine prophylactic CND can be recommended in PTMC patients with independent risk factors of CLNM. Aggressive surgery and close follow-up are essential for patients with risk factors of RFS.